EKSPRESI VISUAL ANAK: REPRESENTASI INTERAKSI ANAK DENGAN LINGKUNGAN DALAM KONTEKS EKOLOGI BUDAYA - Sugiarto, Eko (Universitas Pendidikan Indonesia, 2014)
This research is to fine (1) visual elements, composition, and expression style on children’s drawing in coastal, urban, and mountainous environment in Semarang, (2) representation the sub environment in the children’s drawing in Semarang. Qualitative approach (multi case study) is used in this research. There are two content of the results. First, visual elements, composition, and expression style on children’s drawing in coastal, urban, and mountainous environment in Semarang show each characteristics. Second, attitude, behavior, and values in the coastal, urban, mountain environment not only were drawn explicitly, but also implicitly, that is indicated by the selection of shapes, use of color, organization, and style of the picture. It can be concluded that the expression of the children’s drawing shows